Functional Analysis of Republic of Croatia for Short Sea Shipping Development - Bukljaš Skočibušić, Mihaela; Jolić, Natalija (Promet - Traffic&Transportation, 2012)
From the aspect of the Republic of Croatia, short-sea shipping has multiple significance. Primarily, the short-sea shipping between the Croatian and Italian coast, diverting of a part of cargo that is transported from the European Union into the countries of south-eastern Balkan via Croatia, reduction in harmful emissions in traffic and increase of traffic in the domestic ports. From the aspect of Europe short-sea shipping refers to the movement of goods and passengers by sea between the ports located in Europe or between these ports and the ports outside Europe that have a joint sea border with Europe. The aim of introducing short-sea shipping are: relief of the burden on the European road routes and shift of transport of cargo and passengers to the maritime transport, improvement of traffic connections and competitiveness of Croatia with the European Union, as well as the connection of the Danube and the Adriatic.KEY WORDS: short-sea shipping, Republic of Croatia, maritime routes, traffic corridors